2019
DOI: 10.1177/0379572119833853
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Compliance With Micronutrient Powder and Complementary Food Blend Use by Filipino Mothers and Their Promotion by Community Workers

Abstract: Background: Despite the nationwide micronutrient powder (MNP) supplementation, the Philippines only saw limited success in reducing the prevalence of anemia-a condition that has remained a public health concern among young children. Objective: To assess and explore the acceptability and compliance to MNP and Bigas-Mongo (BigMo) complementary food blend among mothers/caregivers of children aged 6 to 23 months and the promotion of these products by community health workers (CHWs). Methods: This study was part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…They do this by interacting with caregivers and discussing their problems with the programme team (10) . There are some barriers to a successful implementation of MNP interventions, such as misconceptions around MNP, side-effects of MNP and inconsistent supply of MNP product (12) , and regular home visits (expected at least one visit per month) by CHWs might help overcome these (11,29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…They do this by interacting with caregivers and discussing their problems with the programme team (10) . There are some barriers to a successful implementation of MNP interventions, such as misconceptions around MNP, side-effects of MNP and inconsistent supply of MNP product (12) , and regular home visits (expected at least one visit per month) by CHWs might help overcome these (11,29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…Also highly cited was the interventions' ability to prevent disease, illness and malnutrition, with the intervention even being compared with medication (22)(23)(24)(25) , as similarly reported in previous studies (55,57) . Interestingly, when noting improved growth, such as weight, height and strength, some caregivers also noted neurodevelopmental improvements (17)(18)(19)(20)(21)(24)(25)(26)(27)(28)(29)(30)(31)(32) . Caregivers did report organoleptic changes in food (colour, taste, smell and texture) when micronutrient powders were added (29,37) .…”
Section: Discussionmentioning
confidence: 99%
“…One of the most noted reasons for low acceptability was poor communication and/or understanding such as lack of caregiver self-efficacy and forgetfulness, limited social support and/or availability/accessibility to the intervention. Appropriate training of intervention use is essential; in one study, a participant reported stopping the intervention when the infant needed medication, counter to the intention of the study ( 27 ) . One caregiver simply gave no reason, they just did not want to use the intervention, and another cited seeing no impact from the intervention ( 17 , 20 , 26 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expected results have not been obtained due to the absence of qualified personnel to verify and supervise its continuity (8). In Perú, the government has promoted various nutritional programs for several decades, nevertheless, there are still high rates of anemia in several regions of the country (9). Therefore, it is necessary to take measures and join efforts to improve therapeutic adherence to ferrous sulfate, as well as having trained and qualified personnel for their adequate management in the continuous assessment of the effectiveness of these interventions (10,11).…”
Section: Introductionmentioning
confidence: 99%